Early histological changes of pulmonary arterial hypertension disclosed by invasive cardiopulmonary exercise testing. (April 2019) - Bhatti, Yousaf J.; Rice, Alexandra J.; Kempny, Aleksander; Dimopoulos, Konstantinos; Price, Laura C.; Ranu, Harpreet; Wells, Athol; Wort, S. John; McCabe, Colm
Early diagnosis of pulmonary artery hypertension (PAH) is diagnostically challenging given the extent of pulmonary vascular remodeling required to bring about clinical signs and symptoms. Exercise testing can be invaluable in this setting, as stressing the cardiopulmonary system may unmask early disease. This report describes a young patient with a positive family history of PAH in whom contemporaneous invasive cardiopulmonary exercise testing and surgical lung biopsy reveal the novel association between exercise pulmonary hypertension (ePH) and early histological changes of PAH. Exercise PH currently carries no pathological correlates which means the hemodynamic effects of early pulmonary vascular remodeling remain unknown. Following the recent proceedings from the World Symposium in Pulmonary Hypertension 2018, which broaden the hemodynamic definition of PAH, this report suggests an important association between ePH and early pulmonary vascular remodeling supporting a role for exercise hemodynamic evaluation in patients at increased familial risk of PAH.